History Of Early Childhood Educator Development - Kesya Syakirah Putri; Ade Irma; Rennia Syfutri; Evryeni Jusmadi (Jurnal Pendidikan Rafflesia, 2025)
The development of educators in Early Childhood Education (PAUD) institutions in Indonesia experienced a long and dynamic process that reflected the changing paradigm of national education. From the early establishment of preschool institutions to the era of modern educational policies, the role of PAUD educators continuously evolved in response to social, cultural, and technological demands. This article aimed to trace the history and developmental process of PAUD educators in Indonesia through a literature review and secondary analysis of various regulations, government policies, and previous research findings. The results showed that although there had been significant improvements in teachers’ academic qualifications and professionalism, disparities still existed in access to training, certification, and competency enhancement across regions. The greatest challenges emerged in the integration of digital technology and the implementation of curricula that required creative, adaptive, and child-centered pedagogical abilities. Overall, the development process of PAUD educators demonstrated progress but still required synergy among policies, educational institutions, and communities to achieve equitable quality in early childhood education throughout Indonesia.